Comparison of nebulized ketamine and ketamine with clonidine in postoperative sore throat - Jain, Sunita; Bendwal, Hari Prasad; Gohiya, Sarita; Alwani, Neil; Pancholi, Santosh; Romday, Rakesh (International Surgery Journal, 2017)
Background: Postoperative sore throat (POST) consider a minor ailment in patients receiving general anesthesia with endotracheal intubation, seen in 21-65% cases but it causes significant distress and increases postoperative morbidity and patient dissatisfaction. This study was done to compare nebulized ketamine and ketamine with clonidine to treat POST. Methods: This was a prospective, randomized, double-blind control clinical study. After approval from institution ethical and scientific committee, study was conducted in between May 2015-April 2016. Written and informed consent was obtained from 100 patients of either sex aged between 20-65 years. ASA I-II, undergoing surgery in supine position lasting up to two hour. Patients were randomized into two groups Group K (n=50) nebulized with 50 mg ketamine (1cc) + 3cc NS =4cc, Group KC (n=50) nebulized with ketamine 50mg (1cc) + clonidine 150µg (1cc) + 2cc NS for 15 min, before general anaesthesia with endotracheal intubation. The POST and hemodynamic variable were monitored before nebulization, after nebulization, before induction, on arrival to PACU and at 4, 8, 12, 24 hours post operatively. POST was graded on 4 point scale (0-3). Results: Overall incidence of POST was 46% (Group K-40%, KC-6%). The Incidence and severity of POST were significantly attenuated in Group KC in comparison to Group K at 4 hours (P= 0.002), 8 hours (P=0.000), 12 hours (P= 0.000) and at 24 hours (P=0.000). Conclusions: Preoperative nebulization with clonidine and ketamine mixture compared to ketamine is more effective in dealing with postoperative sore throat with no adverse effects.